2019
DOI: 10.1002/jclp.22819
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties and utility of the Responses to Positive Affect questionnaire (RPA) in a sample of people with bipolar disorder

Abstract: Objectives To evaluate the psychometric properties of the Responses to Positive Affect (RPA) questionnaire in a sample of persons with bipolar disorder (BD). Method Cross‐sectional survey study with 107 persons with BD. The original 3‐factor model of the RPA was compared with a 2‐factor model. Construct validity was determined with measures of well‐being, personal recovery, social role participation, and psychopathology and incremental validity was evaluated. Results The fit of the 3‐factor model was acceptabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 69 publications
9
20
1
Order By: Relevance
“…In line with previous studies on positive rumination (e.g. Feldman et al, 2008;Kraiss et al, 2019;Raes et al, 2009), the current study also found that trait emotion-focused and self-focused positive rumination were associated with positive emotions during positive events. Our findings suggest that trait positive rumination is effective for up-regulating everyday positive emotions.…”
Section: The Associations Of Savoring and Positive Rumination With Evsupporting
confidence: 92%
See 3 more Smart Citations
“…In line with previous studies on positive rumination (e.g. Feldman et al, 2008;Kraiss et al, 2019;Raes et al, 2009), the current study also found that trait emotion-focused and self-focused positive rumination were associated with positive emotions during positive events. Our findings suggest that trait positive rumination is effective for up-regulating everyday positive emotions.…”
Section: The Associations Of Savoring and Positive Rumination With Evsupporting
confidence: 92%
“…An individual's trait positive rumination has important implications for the development of psychological disorders (Gilbert, Nolen-Hoeksema, & Gruber, 2013;Kraiss et al, 2019). Previous studies have shown that trait positive rumination was inversely associated with depressive symptoms (Feldman et al, 2008;Raes, Daems, Feldman, Johnson, & Van Gucht, 2009;Young, Sandman, & Craske, 2019).…”
Section: Positive Ruminationmentioning
confidence: 99%
See 2 more Smart Citations
“…Data from two studies were combined for the current study. The first dataset ( n = 119) comes from an online cross‐sectional survey study conducted between April and July 2018 (Kraiss, ten Klooster, et al, 2019 ). The second dataset ( n = 90) was collected between September 2018 and March 2020 for the baseline assessment of a randomized controlled trial (RCT) on the effectiveness of a psychological intervention for patients with BD (Kraiss et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%